Front Matter - Steinmacher, Igor; Marczak, Sabrina; Colanzi, Thelma; Viana, Davi; Teixeira, Leopoldo; Vergilio, Silvia; Barcellos, Monalessa; Machado, Ivan; Marques, Johnny (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de Software, 2024)
Este documento traz o front matter dos Anais do SBES 2024.